Asian horses deepen the MSY phylogeny. (15th January 2018) - Felkel, S.; Vogl, C.; Rigler, D.; Jagannathan, V.; Leeb, T.; Fries, R.; Neuditschko, M.; Rieder, S.; Velie, B.; Lindgren, G.; Rubin, C.‐J.; Schlötterer, C.; et al.
Summary: Humans have shaped the population history of the horse ever since domestication about 5500 years ago. Comparative analyses of the Y chromosome can illuminate the paternal origin of modern horse breeds. This may also reveal different breeding strategies that led to the formation of extant breeds. Recently, a horse Y‐chromosomal phylogeny of modern horses based on 1.46 Mb of the male‐specific Y (MSY) was generated. We extended this dataset with 52 samples from five European, two American and seven Asian breeds. As in the previous study, almost all modern European horses fall into a crown group, connected via a few autochthonous Northern European lineages to the outgroup, the Przewalski's Horse. In total, we now distinguish 42 MSY haplotypes determined by 158 variants within domestic horses. Asian horses show much higher diversity than previously found in European breeds. The Asian breeds also introduce a deep split to the phylogeny, preliminarily dated to 5527 ± 872 years. We conclude that the deep splitting Asian Y haplotypes are remnants of a far more diverse ancient horse population, whose haplotypes were lost in other lineages.